Photoactive Materials: Synthesis, Applications and Technology - Blanche, Pierre-Alexandre (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents a collection of 13 original research articles that focus on the science of light-matter interaction. This area of science has been led to some the greatest accomplishments of the past 100 years, with the discovery of materials that perform useful operations by collecting light or generating light from an outside stimulus. These materials are at the center of a multitude of technologies that have permeated our daily life; every day we rely on quantum well lasers for telecommunication, organic light emitting diodes for our displays, complementary metal-oxide-semiconductors for our camera detectors, and of course a plethora of new photovoltaic cells that harvest sunlight to satisfy our energy needs. In this book, top-rated researchers present their latest findings in the field of nano-particles, plasmonics, semi-conductors, magneto-optics, and holography.